Neural Circuits Involved in Activating Emotions - Stefanescu, Cristina (New Trends in Psychology, 2022)
We are particularly interested in emotions and their regulation for a better functioning in general, both personally and professionally. We believe that a better emotional education would help us in the future as a better understanding of interpersonal relationships. We would like to study this subject even more, starting with scientific research, so that we can fight occupational diseases such as burnout or those in schools such as bullying. In the dialectical behavioral approach, DBT, (Linehan, 2015) are approached those who cannot control their emotions very well, subjects with pathology of borderline Cluster B personalities (DSM 5, 2020). They are taught through skill trainings how to respond emotionally functionally to triggers. In DBT, emotions are defined as short, involuntary, systemic responses to internal and external stimuli. Among the solutions given by this form of therapy we find: mindfulness techniques, balancing emotions, interpersonal efficiency, tolerance to stress. So, starting from the analysis of a borderline patient, I found the theoretical research of the neural circuits involved in activating emotions useful.